التعلم والتعليم في الفكر الإسلامي: رفاعة رافع الطهطاوي انموذجا - عبد الودود, ثناء; مغيط, حوراء عطا (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
Education in Islamic thought is considered one of the fundamental pillars that contributed to the building of Islamic civilization. From its earliest beginnings, it was linked to divine revelation and the prophetic message, and later developed into an organized system within comprehensive scholarly institutions. The contributions of Rifa'a Rafi' al-Tahtawi in the 19th century represent a pioneering attempt to renew Islamic educational thought, as he sought to reconcile Islamic principles with the requirements of modernization and progress. This research explores the educational dimensions of Islamic thought and analyzes al-Tahtawi’s vision of education as a reformist project that integrates authenticity with modernity.